SAT0588 Educational Quality of Knee Arthrocentesis Videos on Youtube. (10th June 2014) - Fischer, J.; Geurts, J.; Valderrabano, V.; Hügle, T.
Abstract : Background: Knee arthrocentesis is a commonly performed diagnostic and therapeutic procedure in rheumatology and orthopedic surgery. Classic teaching of arthrocentesis skills relies on hands-on practice under supervision. Video-based online teaching is an increasingly utilized educational tool in higher and clinical education. YouTube is a popular video-sharing Web site that can be accessed as a teaching source. Objectives: The objective of this study was to assess the educational value of YouTube videos on knee arthrocentesis posted by health professionals and institutions during the period from 2008 to 2012. Methods: The YouTube video database was systematically searched using 5 search terms related to knee arthrocentesis. Two independent clinical reviewers assessed videos for procedural technique and educational value using a 5-point global score, ranging from 1 = poor quality to 5 = excellent educational quality. As validated international guidelines are lacking, we used the guidelines of the Swiss Society of Rheumatology as criterion standard for the procedure. Results: Of more than thousand findings, 13 videos met the inclusion criteria. Of those, 2 contained additional animated video material: one was purely animated, and one was a check list. The average length was 3.31±2.28 minutes. The most popular video had 1388 hits per month. Our mean global score for educational value was 3.1±1.0. Eight videos (62%) were considered useful for teaching purposes. Use of a "no-touch" procedure, meaning that once disinfected the skin remains untouched before needle penetration, was present in all videos. Six videos (46%) demonstrated full sterile conditions. There was no clear preference of a medial (n=8) versus lateral (n=5) approach. Conclusions: A discreet number of YouTube videos on knee arthrocentesis appeared to be suitable for application in a Web-based format for medical students, fellows, and residents. The low-average mean global score for overall educational value suggests an improvement of future video-based instructional materials on YouTube would be necessary before regular use for teaching could be recommended. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1786